Respuesta :

Option D: [tex]$f(x)=-2(x+2)(x-4)$[/tex] is the function

Explanation:

Let the general form of quadratic equation be [tex]$y=a x^{2}+b x+c$[/tex]

The function passes through the intercepts [tex](-2,0)[/tex] and [tex]$(4,0)$[/tex] and also passes though the point [tex]$(-1,10)$[/tex]

Substituting the points [tex](-2,0)[/tex], [tex]$(4,0)$[/tex] and [tex]$(-1,10)$[/tex] in the equation [tex]$y=a x^{2}+b x+c$[/tex], we get,

[tex]4a -2b+c=0[/tex]  -----------(1)

[tex]16a +4b+c=0[/tex] ----------(2)

[tex]a-b+c=10[/tex]    -----------(3)

Subtracting (1) and (2), we get,

[tex]\ \ 4a -2b+c=0\\ 16a +4b+c=0\\\---------\\ \ \ -12a-6b=0[/tex]  -----------(4)

Subtracting (2) and (3), we get,

[tex]16a +4b+c=0\\\ \ a \ \ - \ \ b \ +c=10\\---------\\15a+5b=-10[/tex]  ------------(5)

Multiplying equation (4) by 5 and equation (5) by 4, to cancel the term b when adding, we get,

[tex]-60a-30b=0\\\ 90a+30b=-60\\--------\\30a=-60\\\ \ a=-2[/tex]

Thus, the value of a is [tex]a=-2[/tex]

Substituting [tex]a=-2[/tex] in equation (4), we get,

[tex]$\begin{aligned}-12 a+6 b &=0 \\-12(-2)-6 b &=0 \\ 24-6 b &=0 \\ 24 &=6 b \\ 4 &=b \end{aligned}$[/tex]

Thus, the value of b is [tex]b=4[/tex]

Now, substituting the value of a and b in equation (1), we have,

[tex]$\begin{aligned} 4 a-2 b+c &=0 \\ 4(-2)-2(4)+c &=0 \\-8-8+c &=0 \\ c &=16 \end{aligned}$[/tex]

Thus, the value of c is [tex]c=16[/tex]

Now, substituting the value of a,b and c in the general formula [tex]$y=a x^{2}+b x+c$[/tex], we get,

[tex]y=-2x^{2} +4x+16[/tex]

Taking out the common term as -2 we get,

[tex]y=-2(x^{2} -2x-8)[/tex]

Factoring , we get,

[tex]$y=-2(x+2)(x-4)$[/tex]

Thus, the function is [tex]$f(x)=-2(x+2)(x-4)$[/tex]

Answer:

Option D:

Step-by-step explanation:

ACCESS MORE